2006
DOI: 10.1002/da.20144
|View full text |Cite
|
Sign up to set email alerts
|

Age-related cognitive effects of ECT and ECT-induced mood improvement in depressive patients

Abstract: This explorative study investigated the interaction between electroconvulsive therapy (ECT) treatment-effect, reduced depression, and neuropsychological outcome in relation to age. Follow-up neuropsychological assessment was conducted with depressive patients treated with ECT. From a potential sample of 45 patients, the neuropsychological measures (pre-ECT, three times post-ECT, up to 12 months) and clinical data from the remaining 21 patients who completed all assessments were evaluated (mean age 5 56.76; SD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 47 publications
2
21
0
3
Order By: Relevance
“…This short term improvement was more pronounced in older patients compared to younger patients (<60 years). At the same time, decreased inhibition (frontal function) was seen after a course of ECT (Bosboom and Deijen, 2006).…”
Section: Cognitive Functioning In Mixed Age Groups Post Ectmentioning
confidence: 83%
See 1 more Smart Citation
“…This short term improvement was more pronounced in older patients compared to younger patients (<60 years). At the same time, decreased inhibition (frontal function) was seen after a course of ECT (Bosboom and Deijen, 2006).…”
Section: Cognitive Functioning In Mixed Age Groups Post Ectmentioning
confidence: 83%
“…In general they reported at follow-up (up to 12 months after ECT) for all ages similar improvement of neuropsychological scores. Whereas ECT improved speed of information processing, mental control, memory (all aspects) and perception (visual organization), recovery of depression was especially associated with improvement of memory (verbal learning), higher speed of information processing and improvement of executive functioning (Bosboom and Deijen, 2006).…”
Section: Cognitive Functioning In Mixed Aged Groups At Follow-upmentioning
confidence: 99%
“…This result was not consistent with previous findings in which the mean age of the samples was in the 40s and 50s (Sackeim et al, 2007;Sobin et al, 1995). Bosboom and Deijen (2006) found that the alleviation of depression after ECT was associated with a short-term cognitive improvement that was greater in older patients (≥60 years of age). The markedly negative, but transient, effect of major depression on cognition in a subgroup of elderly individuals who later remit from depression may imply that we were less likely to find such associations in our elderly sample.…”
Section: Discussionmentioning
confidence: 97%
“…Another possible explanation is that stimulation of the neural system results in restorative plasticity, especially in the elderly. 15,17 Because with ECT the elderly are at a disadvantage for disturbance of other kinds of memory (such as short-term memory), restorative plasticity may adhere to specific brain regions. 7,18 Only the scores on WF-2 were significantly affected by electrode placement over time.…”
Section: Discussionmentioning
confidence: 99%